Alternative Splicing Events and Splicing Factors Are Prognostic in Adrenocortical Carcinoma - Lv, Jian; He, Yuan; Li, Lili; Wang, Zhihua (Frontiers in Genetics, 2020)
Changes of the alternative splicing (AS) patterns are closely related to the development of cancer. We investigated alternative splicing events (ASEs) and hub splicing factors (SFs) that related to the prognosis of adrenocortical carcinoma (ACC). The transcriptome data of 79 ACC cases and their corresponding clinical information were downloaded from The Cancer Genome Atlas. Percent Spliced-In (PSI) of seven types of ASEs of 79 ACC cases downloaded from TCGA SpliceSeq. 1839 survival related-ASEs (SR-ASEs) were employed by the univariate Cox regression analysis. Prognostic index (PI) based on seven types of SR-ASEs were calculated by multivariate Cox regression analysis. Survival curves and ROC curves were used to assess the diagnostic value of prognostic model. Independent prognosis analysis showed that THNSL2|54469|ME could accurately predict the prognosis of patients with ACC. 188 highly correlated interaction were selected by correlation analysis of the mRNA level of SFs and PSI of SR-ASEs. Six hub SFs YBX1, SART1, PRCC, SNRPG, SNRPE and SF3B4 were identified. Based on TCGA, GEPIA and GEO, these six hub SFs were significantly related to the overall survival and prognosis of ACC. Overall, we provided a reliable model for predicting the prognosis of ACC patients based on the aberrant AS patterns and hub SFs.